Potential mechanisms and serum biomarkers involved in sex differences in pulmonary arterial hypertension - Li, Chan (Medicine (Baltimore), 2020)
Pulmonary arterial hypertension (PAH) is a disease associated with high mortality, but notable sex differences have been observed between males and females. For this reason, further research on the mechanisms underlying sex differences in PAH is required to better understand and treat the disease. This study mainly focused on gene expression levels to investigate potential differences in the pathogenesis and progression of PAH between the male and female sexes. Sex-specific differentially expressed genes (DEGs) were analyzed using the Gene Expression Omnibus datasets GSE117261 and GSE38267. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were conducted, and a protein-protein interaction (PPI) network was established based on the identified DEGs to predict potential mechanisms involved in the observed sex differences in the pathogenesis of PAH. We identified 26 female- and 53 male-specific DEGs from lung tissue and 498 female-specific DEGs in blood samples. No male-specific DEGs were identified from blood samples. GO and KEGG pathway analyses revealed that female-specific DEGs in lung tissue were enriched in inflammatory response and cytokine-cytokine receptor interaction, whereas male-specific DEGs were mainly enriched in cellular chemotaxis and the nuclear factor of kappa light polypeptide gene enhancer in B-cell (NF-kappa B) signaling pathway. Lipocalin 2 (LCN2) was the only gene that was differentially expressed in both the lung tissue and the blood of female patients. In conclusion, inflammation and immunity may play key roles in the pathogenesis of female PAH, and LCN2 may act as a serum biomarker of female PAH, whereas the pathogenesis in males is more complicated.